2023
DOI: 10.1038/s41467-023-37133-4
|View full text |Cite
|
Sign up to set email alerts
|

Revealing evolution of tropane alkaloid biosynthesis by analyzing two genomes in the Solanaceae family

Abstract: Tropane alkaloids (TAs) are widely distributed in the Solanaceae, while some important medicinal tropane alkaloids (mTAs), such as hyoscyamine and scopolamine, are restricted to certain species/tribes in this family. Little is known about the genomic basis and evolution of TAs biosynthesis and specialization in the Solanaceae. Here, we present chromosome-level genomes of two representative mTAs-producing species: Atropa belladonna and Datura stramonium. Our results reveal that the two species employ a conserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 109 publications
3
10
0
Order By: Relevance
“…Assessing the quality of our assembly, we found that the Datura genome encompassed 97.25% of complete single-copy orthologs (BUSCOs) out of the 255 total BUSCOs searched. Only 5 single-copy orthologs exhibited fragmentation, a level of completeness consistent with both the initial Mexican draft genome and the newly published Chinese D. stramonium genome ( De-la-Cruz et al 2021 ; Zhang et al 2023 ). This consistency in quality assembly statistics emphasizes the robustness and completeness of our assembly.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Assessing the quality of our assembly, we found that the Datura genome encompassed 97.25% of complete single-copy orthologs (BUSCOs) out of the 255 total BUSCOs searched. Only 5 single-copy orthologs exhibited fragmentation, a level of completeness consistent with both the initial Mexican draft genome and the newly published Chinese D. stramonium genome ( De-la-Cruz et al 2021 ; Zhang et al 2023 ). This consistency in quality assembly statistics emphasizes the robustness and completeness of our assembly.…”
Section: Discussionsupporting
confidence: 68%
“…Through the implementation of our workflow, incorporating Omni-C and HiRise scaffolding sequences, we were able to join 18,023 contigs. L90 statistics resulted in 12 scaffolds, each corresponding to the known chromosomes of D. stramonium ( Satina et al 1941 ; Zhang et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using proteomes as input, OrthoFinder separates genes into orthogroups or sets of genes descended from a single gene in the common ancestor of the species under consideration, which includes all orthologs and paralogs. We included 14 sequenced genomes— S. lycopersicum M82_MAS2.0 ( 87 ), S. pimpinellifolium ( 119 ) S. pennellii ( 120 ), S. lycopersicoides ( 121 ), S. tuberosum v6.1 ( 122 ), S. melongena v4.1 ( 123 ), I. cyaneum ( 124 ), Datura stramonium ( 125 ), Lycium barbarum ( 126 ), N. attenuata ( 127 ), P. axillaris ( 128 ), I. trifida ( 129 ), C. canephora ( 130 ), and V. vinifera ( 131 )—and two transcriptomes— S. nigrum ( 55 ) and S. quitoense ( 55 ).…”
Section: Methodsmentioning
confidence: 99%
“…Third, while microorganisms release metabolites into the media, plants tend to store them into the cells, making the recovery of metabolites more difficult. Fourth, the alkaloid synthesis in plants is often tissue-specific, for example, many biosynthetic enzymes for tropane alkaloids biosynthesis are expressed in roots [114]. To overcome this issue it is possible to use differentiated cultures, such as hairy roots.…”
Section: Accepted Manuscriptmentioning
confidence: 99%